2020
DOI: 10.1093/jxb/eraa288
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation mechanisms of metal(loid) stress in plants by silicon: a review

Abstract: Silicon (Si), although not considered as an essential element for plants in general, can ameliorate the phytotoxicity induced by excess metal(loid)s whether non-essential (e.g. Cd, Pb, Cr, Al, As, and Sb) or essential (e.g. Cu, Ni, and Zn). The Si-enhanced resistance allowing plants to cope with this type of abiotic stress has been developed at multiple levels in plants. Restriction of root uptake and immobilization of metal(loid)s in the rhizosphere by Si is probably one of the first defence mechanism. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 164 publications
0
43
0
4
Order By: Relevance
“…In previous investigations, Si resulted in an improvement in the antioxidant system of plants subjected to abiotic stresses [1][2][3]11,12,14,47]. Under Si supply, different biochemical responses during Al exposure such as an increment in antioxidant compounds (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…In previous investigations, Si resulted in an improvement in the antioxidant system of plants subjected to abiotic stresses [1][2][3]11,12,14,47]. Under Si supply, different biochemical responses during Al exposure such as an increment in antioxidant compounds (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, since hormesis can also result in phenotypic changes and adaptation strategies in plants under challenging environments ( Macias-Bobadilla et al, 2020 ), this phenomenon has the potential to enhance agricultural sustainability in a changing world ( Agathokleous & Calabrese, 2019 ). Importantly, even under non-stressful environmental conditions, Si has been proven to stimulate plant growth and metabolism ( Trejo-Téllez et al, 2020 ; Xu et al, 2020 ), though its beneficial effects are more evident under stress conditions ( Ahanger et al, 2020 ; Bui, Duong & Nguyen, 2020 ; Mandlik et al, 2020 ; Singh et al, 2020 ; Vaculík et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that non-enzymatic antioxidants, such as non-protein thiol and total glutathione, were upregulated by H 2 S and improved Pb tolerance by ROS-scavenging and/or directly chelating metal ions. Plant exposure to metal ions often represses the activity of transporters, resulting in ionic imbalance and reduced nutrients assimilation in plants (Vaculík et al, 2020). In Zn-exposed pepper plants, exogenous NaHS treatment reduced Zn plant accumulation and enhanced the absorption of key mineral elements, i.e., Fe, N, P .…”
Section: Exogenous H 2 S Application: a Precursor Of Heavy Metal Strementioning
confidence: 99%